PELATIHAN PEMBUKUAN KEUANGAN DAN PEMASARAN ONLINE BAGI PENGRAJIN DAUN LONTAR DI DESA TINDANG, KABUPATEN GOWA, SULAWESI SELATAN - haerana haerana; Abdi Abdi; Burhanuddin Burhanuddin (LPPM Universitas Abdurrab, 2023)
Palm leaf craft is a small business craft made from palm leaves and the frame of the craft is made of bamboo. This craft is manifested in the form of a cake/food cover which is often called